On Oscillatory and Asymptotic Behavior of a Second-Order Nonlinear Damped Neutral Differential Equation - Ercan Tunç; Said R. Grace (International Journal of Differential Equations)
This paper discusses oscillatory and asymptotic properties of solutions of a class of second-order nonlinear damped neutral differential equations. Some new sufficient conditions for any solution of the equation to be oscillatory or to converge to zero are given. The results obtained extend and improve some of the related results reported in the literature. The results are illustrated with examples.